Advances in the application of multi-omics analysis in skin aging - Long, Boquan; Pan, Weitian; Wu, Shuozhong; Nong, Qianye; Li, Wenhui; Chen, Siqi; Guo, Hongwei (Frontiers in Aging, 2025)
Skin aging is a progressive decline in the structural integrity and physiological function of the skin, driven by a complex interplay of intrinsic and extrinsic factors. Consequently, skin aging is classified into intrinsic and extrinsic aging. Intrinsic aging is characterized by epidermal thinning, dryness, fine lines, and reduced elasticity over time, whereas extrinsic aging manifests as epidermal thickening, deep wrinkles, skin laxity, roughness, and pigmentation, particularly in sun-exposed areas, such as the face, neck, and hands. The underlying mechanisms of these two aging processes are intricate and distinct, encompassing various elements, including temporal aspects, genetic predisposition, immune responses, endocrine influences, and ultraviolet radiation. Multi-omics approaches—including macro-genomics, epigenetics, transcriptomics, proteomics, and metabolomics—offer valuable insights into the mechanisms and pathogenesis of skin aging while aiding in the identification of biomarkers and potential therapeutic targets. This review provides an overview of advancements in skin aging research using multi-omics technologies, aiming to foster innovation in research methodologies related to skin aging.